Numerical and experimental investigation of turbocharger compressor low-end performance improvement using a variable geometry inlet orifice. (August 2021) - Zhao, Ben; Zhao, Qingjun; Zhao, Wei; Xiang, Xiaorong; Zhou, Xiaoyong
Variable geometry orifice located upstream of a centrifugal impeller has been proposed to improve compressor low-end performance, by reducing compressor inlet flow area. The inlet flow area reduction is achieved by actuating the orifice flow area. The effects of the flow area reduction on compressor performance and the physical mechanisms controlling performance were investigated in the current work using numerical simulations and physical experiments. At the investigated compressor speed, with reduced inlet flow area, compressor efficiency at high flow rates is decreased by 2.01 percentage points based on the numerical predictions and by 6.47 percentage points based on the physical data. At low flow rate, however, compressor efficiency can be improved by 2.26 percentage points based on the numerical predictions and by 2.88 percentage points based on the physical data. Besides the efficiency, the inlet flow area reduction shifts the compressor stability limit toward the lower flow rate by 9.09% based on the numerical results and 41.13% based on the physical experiment and improves the compressor peak pressure ratio by 0.55% based on both the numerical and experimental data. At the flow rates lower than the peak efficiency point, it is beneficial to actuate the orifice to improve the compressor low-end performance. At flow rates higher than the peak efficiency point, it is necessary to deactivate the orifice to avoid the inlet flow area reduction that induces flow loss and degrades compressor performance.